Temporal envelope processing in the human auditory cortex: Response and interconnections of auditory cortical areas - Gourévitch, Boris; Le Bouquin Jeannès, Régine; Faucon, Gérard; Liégeois-Chauvel, Catherine (Hearing research, 2008)
Temporal envelope processing in the human auditory cortex has an important role in language analysis. In this paper, depth recordings of local field potentials in response to amplitude modulated white noises were used to design maps of activation in primary, secondary and associative auditory areas and to study the propagation of the cortical activity between them. The comparison of activations between auditory areas was based on a signal-to-noise ratio associated with the response to amplitude modulation (AM). The functional connectivity between cortical areas was quantified by the directed coherence (DCOH) applied to auditory evoked potentials. This study shows the following reproducible results on twenty subjects: (1) the primary auditory cortex (PAC), the secondary cortices (secondary auditory cortex (SAC) and planum temporale (PT)), the insular gyrus, the Brodmann area (BA) 22 and the posterior part of T1 gyrus (T1Post) respond to AM in both hemispheres. (2) A stronger response to AM was observed in SAC and T1Post of the left hemisphere independent of the modulation frequency (MF), and in the left BA22 for MFs 8 and 16 Hz, compared to those in the right. (3) The activation and propagation features emphasized at least four different types of temporal processing. (4) A sequential activation of PAC, SAC and BA22 areas was clearly visible at all MFs, while other auditory areas may be more involved in parallel processing upon a stream originating from primary auditory area, which thus acts as a distribution hub. These results suggest that different psychological information is carried by the temporal envelope of sounds relative to the rate of amplitude modulation.